Fengreqing Oral Liquid Exerts Anti-Inflammatory Effects by Promoting Apoptosis and Inhibiting PI3K/AKT and NF-κB Signaling Pathways - Rao, Zhili; Li, Xiangyu; Zhang, Xia; Zeng, Jiuseng; Wang, Baojun; Yang, Ruocong; Zeng, Nan (Frontiers in Pharmacology, 2022)
Fengreqing oral liquid(FOL), a proprietary Chinese medicine used in clinical practice in China frequently, is effective in treating inflammatory diseases of the upper respiratory tract such as colds and flu. However, its anti-inflammatory effects and mechanisms remains to be elucidated. In this study, the anti-inflammatory effects of FOL and its mechanism on PI3K/AKT and NF-κB signaling pathways in LPS-induced RAW264.7 cells were explored, and also the regulatory effect of FOL on apoptosis. In addition, the potential of FOL for the treatment of acute lung injury was explored in LPS-induced ALI mice. The results showed that treatment with FOL significantly reduced the levels of interleukin 1β(IL-1β), interleukin 6(IL-6), nitric oxide(NO) and tumor necrosis factor α(TNF-α) in the supernatant of LPS-induced RAW264.7 cells, and also significantly reduced the phosphorylated protein levels of PI3K and AKT in PI3K/AKT signaling pathway and also NF-κB p50 protein, phosphorylated NF-κB p65 and IκBα in the NF-κB signaling pathway. In addition, the results showed that FOL induced apoptosis in LPS-induced RAW264.7 cells at level of 80-90%, and significantly increased the protein expression levels of the pro-apoptotic Bax and cleaved-caspase-3. In LPS-induced ALI mice, FOL administration showed inhibition of IL-1β，IL-6 and TNF-α in BALF and decreased protein expression levels of PI3K, AKT, NF-κB p50 and NF-κB p65, and elevated protein expression levels of Bax and cleaved-caspase-3 significantly. These results suggest that FOL may exert anti-inflammatory effects by inhibiting the PI3K/AKT signaling pathway to promote apoptosis and leading to attenuated activation of the NF-κB signaling pathway.